2022
DOI: 10.5051/jpis.2106260313
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid CSF-1 and IL-34 levels in patients with stage III grade C periodontitis and uncontrolled type 2 diabetes mellitus

Abstract: Purpose Periodontal diseases are inflammatory conditions that alter the host’s response to microbial pathogens. Type 2 diabetes mellitus (T2DM) is a complex disease that affects the incidence and severity of periodontal diseases. This study investigated the gingival crevicular fluid (GCF) levels of colony-stimulating factor-1 (CSF-1) and interleukin-34 (IL-34) in patients with stage III grade C periodontitis (SIII-GC-P) and stage III grade C periodontitis with uncontrolled type 2 diabetes (SIII-GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…As a result of these ndings, it can be suggested that IL-34 and M-CSF may have similar functional properties in periodontal disease. Dikilitaş et al reported that there were no differences at IL-34 levels in GCF between patients with healthy periodontium and Stage III Grade C periodontitis, but they were at high levels in periodontitis patients with uncontrolled diabetes [11]. On the other hand, Batra et al [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of these ndings, it can be suggested that IL-34 and M-CSF may have similar functional properties in periodontal disease. Dikilitaş et al reported that there were no differences at IL-34 levels in GCF between patients with healthy periodontium and Stage III Grade C periodontitis, but they were at high levels in periodontitis patients with uncontrolled diabetes [11]. On the other hand, Batra et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies in the literature evaluating M-CSF in GCF. Dikilitaş et al reported that the M-CSF-1 level in GCF was higher than patients with Stage III Grade C periodontitis and diabetes compared to healthy individuals [11]. Lira Junior et al stated higher levels of M-CSF in the peri-implant sulcus at periimplantitis compared to the peri-implant mucositis, and suggested M-CSF can be a diagnostic marker for peri-implant disease [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging cohort studies have reported that the expression patterns of IL‐34 are dramatically elevated in gingival crevicular fluid (GCF) collected from patients with periodontitis (Adamopoulos & Mellins, 2015; Bozkurt Dogan et al., 2021; Dikilitas et al., 2022; Guruprasad & Pradeep, 2018b). Elevated expression of IL‐34 was also identified in multiple myeloma lesions, increasing the rate of RANKL‐mediated osteoclastogenesis, thereby promoting inflammatory osteolysis (Baghdadi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009’s Gum Day, the Korean Academy of Periodontology has promoted oral health by working with regional public health departments to carry out prevention-focused initiatives as part of a goal to raise public awareness of periodontal disease [ 1 ]. The link between systemic disease and periodontitis has been explored in previous studies [ 2 3 ]. Moreover, national health management programs relating to noncommunicable and periodontal diseases have established a new model of a disease management system [ 4 ].…”
mentioning
confidence: 99%